Stabilisation analysis of slope on bauxite mining area - Mohd Fakhrurrazi, Ishak; Shaedon, S.; Noor Asiah, Mohamad; M.H., Zainal Abidin (Asian Research Publishing Network (ARPN), 2016)
Unexpected slope failure has the potential to the most costly form of failure as it leads to safety issues (loss of life) and sometime required time consuming remediation. A work over survey of on TNB substation at Kg Padang, Kuantan revealed a significant movement and failure of a slope within vicinity of excavation works. Ground investigation was conducted to establish information within underlying strata consists of GRAVEL and clayey SILT with traces of sandy which dominantly from residual soil. Laboratory testing and soil investigation are gather as an input parameter to propose a slope and analysis for stabilization. The analysis of slope stabilization reduced the hazard of further work involving cutting and trimming on mining area. Sensitivity study for angle of slope is to address the most effective and suitable for maximize extracting bauxite ore. Reducing slope gradient with improved site drainage to ensured safety for TNB substation was implementing as a remedial works from this study.